The Implementation of Internet-Based Activities in Teaching Listening Skill - Tri Wahyuni Chasanatun (Universitas PGRI Madiun, 2013)
This article aims to discuss about the used of internet-based activities in teaching listening skill. Internet technology is widely spead through all over the world. Many people used internet as their sources in gaining more information. Moreover for the teachers or lecturers of English Language Teaching class, they are using internet technology as their sources or media in teaching and learning process. Hopefully, this article can give contribution to the teacher and lecturer in teaching listening skill.